CBCT analysis of crestal soft tissue thickness before implant placement and its relationship with cortical bone thickness - Xiaoxi Cui; Tyler Reason; Vanessa Pardi; Qiang Wu; Acela A. Martinez Luna (BMC, 2022)
Abstract Background The importance of crestal soft tissue thickness and its influence in peri-implant tissue health has been evaluated in few clinical studies. Cone beam computed tomography imaging offers a unique opportunity to investigate variations in crestal soft tissue thickness. The aim of this retrospective study was to evaluate the possible correlation between crestal soft tissue thickness and hard tissue measurements on CBCT images, and to compare crestal soft tissue thickness among different patients and edentulous site groups. Methods CBCT images of partially edentulous adult patients treated at ECU School of Dental Medicine were evaluated. 267 patients with 321 edentulous sites were included. Demographic data were collected from electronic health records. Cross-sectional CBCT images at the center of each edentulous site were used to measure soft tissue and hard tissue parameters. Linear mixed models were used to compare crestal soft tissue thickness and hard tissue measurements by gender, age groups, and edentulous sites. Pearson correlation was applied to evaluate the correlation between crestal soft tissue thickness and different hard tissue measurements. Association between crestal soft tissue thickness and independent variables (gender, age groups, edentulous sites) was evaluated using repeated measure logistic regression, while the crestal soft tissue thickness was dichotomized by a threshold of 2 mm. Results Mean age of patients included was 60 (range 21-85 years). Female to male ratio was 1.07. Mean crestal soft tissue thickness of all non-grafted native bone sites was 2.17 mm. Mean thickness of cortical bone at alveolar crest was 0.94 mm. Thickness of buccal and lingual cortical plates 5 mm apical to alveolar crest were 1.17 mm and 1.58 mm, respectively. Pearson's correlation showed moderate positive correlation among hard tissue measurements, but weak correlation between soft tissue thickness and hard tissue measurements. Anterior sites [OR = 3.429 (1.100-10.69)] and maxillary posterior sites [OR = 1.937 (1.077-3.482)] had higher odds of presenting with more than 2 mm of soft tissue at the alveolar crest. Conclusion More than half of the patients had crestal soft tissues at edentulous sites thicker than 2 mm. Thickness of crestal soft tissue was not significantly associated with hard tissue measurements. Edentulous anterior sites and maxillary posterior sites presented with thicker crestal soft tissue at alveolar crest as compared to mandibular posterior sites.